A methods engineering study on Anglo Watsons Glass, Inc. - Daño, Maribe; Ferrer, Pedr.; Gadong, Ma. The.; Utanes, Noe. (Diliman, Quezon City College of Engineering, 2005)
A methods engineering study was conducted in Anglo Watsons Glass, Inc, a manufacturer of glass bottles and jars, to find areas where they could improve in order to increase their efficiency in production without sacrificing the quality of the liquor bottles that they manufacture. The scope of the study is the production line that produces the 375 mL liquor bottle. The focus of the study, specifically, is on the inspection and packaging area of the aforementioned product line. In conducting the study, the safety and the working conditions of the workers were also considered. The group documented the present system of the company. The documentations are the production system framework, organizational structure and job descriptions, the products, production process and materials, plant layout and work design. The group used the operation process charts, flow process chart, and two-hand process chart to aid them further in the study. The problems were identified and with the use of the stream diagnostic diagram, five problems were identified as core problems. These are inefficient product handling, lenient supervision, unfavorable working condition, repetition of work, and uneven floor surface. Alternative solutions were established to help find solutions for the core problems using the Kepner- Tregoe approach, where the must and want objectives were identified. A decision analysis method was used to find the best recommendation that could respond to the immediate problem of the plant as well as beneficial in the long run. The recommenations of the group are installation of fixtures, providing safe and effective handling materials, active participation of the management and training the supervisors, fixing the lighting and ventilation of the plant, rotation of workers and installing a wooden pathway for the mini forklifts. In the selection of the recommendations, the group took into account the cost and ease of implementing it. Implementing the said recommendation will increase worker's efficiency and lessens the worker's unproductive time. This would also means an increase in the company's productivity.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 32 : Methods Engineering
Keywords: Glass manufacture; Systems analysis